2013
DOI: 10.1111/mcn.12073
|View full text |Cite
|
Sign up to set email alerts
|

‘It was caused by the carelessness of the parents’: cultural models of child malnutrition in southern Malawi

Abstract: Parents' conceptions of child growth, health and malnutrition are culturally bound, making information about local understandings of malnutrition and its causes necessary for designing effective nutrition programmes. This study used ethnographic methods to elucidate cultural models of child care and malnutrition among the Yao of southern Malawi. Data were collected in six rural villages from 28 key informant interviews with village chiefs and traditional healers among others and 18 focus group discussions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…). A more recent ethnographic study from southern Malawi found that among the Yao people, child malnutrition can be seen as an indication of inadequate parental care, such as poor food provisioning or failure to abide by rules governing sexual abstinence (Flax ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…). A more recent ethnographic study from southern Malawi found that among the Yao people, child malnutrition can be seen as an indication of inadequate parental care, such as poor food provisioning or failure to abide by rules governing sexual abstinence (Flax ).…”
Section: Discussionmentioning
confidence: 99%
“…). A final hypothesis, as seen among mothers of wasted children in Pakistan, some communities that stigmatize epilepsy, and the recent ethnography from Malawi, involves the presence of a belief system that views the condition as a form of supernatural or spiritual punishment (Mull ; Baskind & Birbeck ; Flax ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors, such as lack of funds for transport to a health facility or need to obtain permission from a male relative, often delay or may even thwart health care seeking (Geldsetzer et al, 2014; Kalembo & Zgambo, 2012). Cultural models of illness that blame parents when a child has signs of severe acute malnutrition, such as wasting or edema, can influence the type and timing of health care seeking (Flax, 2015; Howard & Millard, 1997; Mull, 1991). The ability of parents to identify that their child is undernourished based on perceptions of child body size or other physical signs may also play a role in decisions to seek care for the child.…”
Section: Introductionmentioning
confidence: 99%